Rapid self-healing, multiple recyclability and mechanically robust plant oil-based epoxy resins enabled by incorporating tri-dynamic covalent bonding. Issue 34 (19th August 2021) - Zhang, Chaoqun; Wang, Xiao; Liang, Dunsheng; Deng, Henghui; Lin, Zirun; Feng, Pengju; Wang, Qingwen
Abstract : Novel bio-based epoxy resins with high tensile strength, rapid self-healing and excellent multiple recyclability were synthesized through thiol–epoxy "click" reaction between epoxidized vegetable oils and dithiol-functionalized boronic ester. Abstract : The establishment of both mechanically robust yet facile healable and recyclable epoxy resin systems are highly desirable and still present significant challenges. Herein, by fully utilizing epoxidized vegetable oils and dithiol modified boronic ester via the thermally-induced "thiol–epoxy" click reaction, novel plant oil-based epoxy resins were successfully synthesized by incorporating units of dioxaborolane metathesis, transesterification and disulfide metathesis. Reasonably tuning the content of the flexible long fatty acid chains and phenylboronic ester, the plant oil-based epoxy resins possessed highly crosslinking structures and comparable mechanical properties to the conventional epoxy resins, with the tensile strength of up to 43.2 MPa and the elongation at break up to 25%. Moreover, the epoxy resins well embodied dynamic dioxaborolane, disulfide bonds and soft long fatty acid chains, which facilitated facile healing ability and reprocessability at mild conditions. The self-healing efficiency of bio-based epoxy resins could reach 90% at room temperature in 24 h. Further, the mechanical properties of the recycled resins were maintained at 80% of original resins even after 9 times repeated reprocessing.